2020
DOI: 10.7150/ijbs.36595
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus miR-BART1-3p suppresses apoptosis and promotes migration of gastric carcinoma cells by targeting DAB2

Abstract: Although Epstein-Barr virus (EBV) is known to encode over 40 different miRNAs of its own, the roles of most EBV miRNAs remain unknown. Disabled homolog 2 (DAB2) is a putative tumor suppressor, but its role in gastric carcinoma (GC), especially in EBV-associated GC, needs to be clarified. Our qRT-PCR and mRNA microarray results showed that DAB2 expression was down-regulated in EBV-positive GC cells compared to EBV-negative cells. Four BART miRNAs that might target DAB2 were predicted, and we found, using a luci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…These findings suggest that miR-BART1-3p increases resistance to DNA-damage-induced apoptosis by affecting E2F3. Previously, we showed that miR-BART1-3p can inhibit cell apoptosis by acting on disabled homolog 2 (DAB2) in addition to E2F3 [11], suggesting that miRNAs fine tune cell function by targeting multiple genes with overlapping functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that miR-BART1-3p increases resistance to DNA-damage-induced apoptosis by affecting E2F3. Previously, we showed that miR-BART1-3p can inhibit cell apoptosis by acting on disabled homolog 2 (DAB2) in addition to E2F3 [11], suggesting that miRNAs fine tune cell function by targeting multiple genes with overlapping functions.…”
Section: Discussionmentioning
confidence: 99%
“…The EBV miRNA miR-BART1-3p is one of the most highly expressed miRNAs in EBV-associated carcinomas such as GC and NPC [9,10]. Recently, we showed that transfection of a miR-BART1-3p mimic into gastric carcinoma cells caused the cells to accumulate at the G0/G1 phase and suppressed cell apoptosis by suppressing DAB2 [11].…”
Section: Introductionmentioning
confidence: 99%
“…Dab2 is involved in suppression of apoptosis by Epstein-Barr virus (EBV) (40). Two nodes, mitochondrial antiviral signaling protein (MAVS) and DExD/H-Box Helicase 58 (DDX58) were reported as antiviral proteins (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Dab2 is involved in suppression of apoptosis by Epstein-Barr virus (EBV) (40). Two nodes, mitochondrial antiviral signaling protein (MAVS) and DExD/H-Box Helicase 58 (DDX58) were reported as antiviral proteins (41,42). Inhibition of MAVS expression decreased e cacy of hydroxychloroquine against dengue virus (42).…”
Section: Discussionmentioning
confidence: 99%